Application of Green Architecture in Tourist Park in Pasuruan City as a Recreation and Education - Ardhianty, Elsa Juliana; Widjajanti, Wiwik Widyo; Salisnanda, Randy Pratama (Journal of Civil Engineering, Planning and Design, 2025)
The design of the Tourist Park in Pasuruan as a recreational and educational facility aims to create a tourist attraction for entertainment as well as providing education or knowledge for visitors from children to adults. Several facilities are presented, including a flower garden, play zones such as indoor and outdoor playgrounds and there is an education zone that supports culture-based learning such as displaying various 2D and 3D examples of various batik motifs typical of Pasuruan and other regions as well as providing a place to learn about making them. In addition, the design of this tourism park also considers aspects of comfort and accessibility by providing pedestrian paths that are friendly to all ages, fairly large green spaces, and recreational facilities such as indoor and outdoor children's play areas, water play, and culinary centers based on local products. The application of green architectural principles and sustainable use of resources is the main focus in designing this park, so that it can support environmental conservation while increasing the tourist attraction of Pasuruan. Through an innovative and education-based design approach, this tourism park is expected to become a leading tourism icon in Pasuruan that not only attracts tourists, but also provides social, economic, and environmental benefits for the local community. In this way, this park can become a model for sustainable tourism development that supports the growth of the tourism and education sectors in Indonesia.